1870 W. Va. Code 703 - (:unkn) unknown (My University, 1870)
Ch. 153, § 3(8): "If any person go armed with a deadly or dangerous weapon, without reasonable cause to fear violence to his person, family, or property, he may be required to give a recognizance, with the right of appeal, as before provided, and like proceedings shall be had on such appeal."
Keywords: GOING ARMED; SURETY